Asuhan Keperawatan Pada Tn. S Dengan Gangguan Sistem Perkemihan: Chronic Kidney Disease Di Ruang Gladiol AtasRumah Sakit Umum Daerah Sukoharjo - LISTIANI, IDA; , Fahrun Nur Rosid, S.Kep., Ns., M.Kes (2015)
Background : An increasingly consumerist attitudes of humans towards food containing foreign substance harmful to the body the more damning work of the kidney causing disease chronic kidney disease. Globally in 2007 more than 500 million people experiencing chronic kidney disease, in Indonesia 2008 was dead 100.000, in central java 2008 reached 16.954 cases, and in Sukoharjo regency 2008 reached742 cases of chronic kidney disease. Of the various causes leading to chronic kidney disease will bring up various complications and a life time handling therefore nurses is very important in doing the nursing care of patient on chronic kidney disease. Goal : To understand the concept of disease chronic kidney disease as well as able to do nursing care patient chronic kidney disease. Method : The method used is to approach a case study that is the scientific method thay is collect file, analize file, and draw conclusion. Result : The diagnosis appears on the case is a pattern of ineffective breath, excess fluid volume and nutritional imbalances less than body requirements. After nursing care 3x24 hours shortness of breath is reduced, still there is edema, nausea is reduced so that the issue is resolved in part. Conclusion : Nursing care in the conduct of all issues resolved in part so as to require further treatment and cooperation with other medical team, patient and families are indispensable to the success of nursing care.